The spatial network of megaregions - Types of connectivity between cities based on settlement patterns derived from EO-data. (November 2015) - Taubenböck, H.; Wiesner, M.
Abstract: Megaregions are important phenomena of globalization's new urban scale and form. These regions are considered the drivers of global economy, innovation, technology and the labor market. In combination with the global megatrend of urbanization, new dimensions and patterns are evolving conceptualized e.g. by this term 'megaregion'. Using multi-source and multi-temporal satellite data we classify urban footprints and their spatial evolution since the 1970s of five selected megaregions across the globe, namely the megaregions of Southern California anchord by Los Angeles in USA and the Mexican border area, the mega-region São Paulo–Rio de Janeiro in Brazil, the Nile delta anchord by Cairo in Egypt, the mega-region Amsterdam–Rotterdam, Ruhr–Cologne, Brussels–Antwerp and Lille in Europe, and the megaregion Guangzhou–Shenzhen–Hong Kong in China. Based on this geospatial data set, we develop a spatial metric to measure spatial connectivity between cities based on the continuity of settlement patterns. The network of cities within the particular megaregions is based on demographic information. The result is on the one hand an evaluation of the spatial continuity of settlements between the cities within the networks. On the other hand, comparisons whether the settlement patterns in megaregions across the globe are similar or not are performed. We conclude with the finding that three types of megaregions can be spatially classified and one suggested megaregion is spatially not yet connected. Highlights: Characterization of the multitemporal evolution of settlement patterns in megaregions EO-based large area and long-time multi-temporal classifications of urban patterns for 5 megaregions across the globe Empirical spatial analysis of settlement patterns to analyze a spatial unit which is in literature economically defined A method using spatial metrics for measuring consistently spatial patterns and comparing them across the globe